Layer-separated distribution of nitrogen doped graphene by wrapping on carbon nitride tetrapods for enhanced oxygen reduction reactions in acidic medium - Unni, SreeKuttan M.; Illathvalappil, Rajith; Gangadharan, Pranav K.; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Chemical Communications, 2014)
Layer-separated 3D nitrogen doped graphene (NG) with an accessible interstitial surface and modulated activity characteristics for oxygen reduction in acidic medium could be prepared by wrapping NG sheets on in situ generated carbon nitride (CNx) tetrapods.

Layer-separated MoS2 bearing reduced graphene oxide formed by an in situ intercalation-cum-anchoring route mediated by Co(OH)(2) as a Pt-free electrocatalyst for oxygen reduction - Illathvalappil, Rajith; Unni, SreeKuttan M.; Kurungot, Sreekumar (Nanoscale, 2015)
A significant improvement in the electrochemical oxygen reduction reaction (ORR) activity of molybdenum sulphide (MoS2) could be accomplished by its layer separated dispersion on graphene mediated by cobalt hydroxide (Co(OH)(2)) through a hydrothermal process (Co(OH)(2)-MoS2/rGO). The activity make-over in this case is found to be originated from a controlled interplay of the favourable modulations achieved in terms of electrical conductivity, more exposure of the edge planes of MoS2 and a promotional role played by the coexistence of Co(OH)(2) in the proximity of MoS2. Co(OH)(2)-MoS2/rGO displays an oxygen reduction onset potential of 0.855 V and a half wave potential (E-1/2) of 0.731 V vs. RHE in 0.1 M KOH solution, which are much higher than those of the corresponding values (0.708 and 0.349 V, respectively) displayed by the as synthesized pristine MoS2 (P-MoS2) under identical experimental conditions. The Tafel slope corresponding to oxygen reduction for Co(OH)(2)-MoS2/rGO is estimated to be 63 mV dec(-1) compared to 68 mV dec(-1) displayed by the state-of-the-art Pt/C catalyst. The estimated number of electrons transferred during oxygen reduction for Co(OH)(2)-MoS2/rGO is in the range of 3.2-3.6 in the potential range of 0.77 V to 0.07 V, which again stands out as valid evidence on the much favourable mode of oxygen reduction accomplished by the system compared to its pristine counterpart. Overall, the present study, thus, demonstrates a viable strategy of tackling the inherent limitations, such as low electrical conductivity and limited access to the active sites, faced by the layered structures like MoS2 to position them among the group of potential Pt-free electrocatalysts for oxygen reduction.

Lithium-assisted proton conduction at 150 degrees C in a microporous triazine-phenol polymer - Nandi, Shyamapada; Dhavale, Vishal M.; Shalini, Sorout; Werner-Zwanziger, Ulrike; Singh, Harpreet; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Materials Interfaces, 2015)
Keywords: conduction; hydrophobic polar frameworks; lithiated polymers; proton conduction; triazine-phenol polymers

Low surface energy plane exposed co3o4 nanocubes supported on nitrogen-doped graphene as an electrocatalyst for efficient water oxidation - Singh, Santosh K.; Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)

Low band gap benzimidazole COF supported Ni3N as highly active OER catalyst - Nandi, Shyamapada; Singh, Santosh Kumar; Mullangi, Dinesh; Illathvalappil, Rajith; George, Leena; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2016)
Covalent organic frameworks (COFs) have structures and morphologies closely resembling graphenes, whose modular construction permits atomiclevel manipulations. This, combined with their porous structure, makes them excellent catalyst supports. Here, the high electrocatalytic activity of a composite, formed by supporting Ni3N nanoparticles on a benzimidazole COF, for oxygen evolution reaction is shown. The composite oxidizes alkaline water with a near-record low overpotential of 230 mV @ 10 mA cm(-2) (eta(10)). This high activity is attributed to the ability of the COF to confine the Ni3N nanoparticles to size regimes otherwise difficult to obtain and to its low band gap character (1.49 eV) arising from the synergy between the conducting Ni3N nanoparticles and the pi-conjugated COF. The COF itself, as a metalfree self-standing framework, has an oxygen evolution reaction activity with 10 of 400 mV. The periodic structure of the COF makes it serve as a matrix to disperse the catalytically active Ni3N nanoparticles favoring their high accessibility and thereby good charge-transport within the composite. This is evident from the amount of O-2 evolved (230 mmol h(-1) g(-1)), which, to the best of our knowledge, is the highest reported. The work reveals the emergence of COF as supports for electrocatalysts.

Low-overpotential electrocatalytic water splitting with noble-metal-free nanoparticles supported in a sp(3) n-rich flexible COF - Mullangi, Dinesh; Dhavale, Vishal M.; Shalini, Sorout; Nandi, Shyamapada; Collins, Sean; Woo, Tom; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2016)
Covalent organic frameworks (COFs) are crystalline organic polymers with tunable structures. Here, a COF is prepared using building units with highly flexible tetrahedral sp(3) nitrogens. This flexibility gives rise to structural changes which generate mesopores capable of confining very small (<2 nm sized) non-noble-metal-based nanoparticles (NPs). This nanocomposite shows exceptional activity toward the oxygen-evolution reaction from alkaline water with an overpotential of 258 mV at a current density of 10 mA cm(-2). The overpotential observed in the COF-nanoparticle system is the best in class, and is close to the current record of approximate to 200 mV for any noble-metalfree electrocatalytic water splitting system-the Fe-Co-Ni metal-oxide-film system. Also, it possesses outstanding kinetics (Tafel slope of 38.9 mV dec(-1)) for the reaction. The COF is able to stabilize such small-sized NP in the absence of any capping agent because of the COF-Ni(OH)(2) interactions arising from the N-rich backbone of the COF. Density-functional-theory modeling of the interaction between the hexagonal Ni(OH)(2) nanosheets and the COF shows that in the most favorable configuration the Ni(OH)(2) nanosheets are sandwiched between the sp(3) nitrogens of the adjacent COF layers and this can be crucial to maximizing their synergistic interactions.